Floristic Composition and Biological Spectrum of The Bogdkhan Mountain, Mongolia (Bangladesh Journal of Plant Taxonomy, 2022)
The Bogdkhan mountain of Mongolia is strictly protected and possesses a unique ecosystem, because of its location in the transitional zone of Siberian taiga and the Asian steppe. Floristic composition and the biological spectrum of the Bogdkhan Mountain were studied during July 2019 to September 2020. A total of 522 vascular plants were recorded belonging to 249 genera and 63 families. Asteraceae was found to be the most dominant family (13.22%; 33 genera and 69 taxa) followed by Poaceae (8.43%; 21 genera and 44). The classified life-form spectra of all the species recorded from the study area revealed the predominance of hemicryptophytes (63.03%) followed by geophytes (11.30%), therophytes (10.34%), phanerophytes (9.58%), chamaephytes (5.36%), and hydrophytes (0.38%). The notable changes found in the biological spectrum, which are chamaephytes from 12 to 5.36%, geophytes from 8 to 11.30% and therophytes from 8 to 10.34%. Variaty of reasons might cause change the life form, such as climate change, anthropogenic impacts, etc. Hemicryptophytes and chamaephytes dominate the flora of the mountain due to the cold mountain niche. The floristic diversity of this mountain tends to decline further videnced from the observed lesser divergence values of geophytes and therophytes.Bangladesh J. Plant Taxon. 29(2): 241-268, 2022 (December)